A Comprehensive Review on Controlling Surface Composition of Pt‐Based Bimetallic Electrocatalysts. Issue 20 (14th April 2018) - Zhang, Bin‐Wei; Yang, Hui‐Ling; Wang, Yun‐Xiao; Dou, Shi‐Xue; Liu, Hua‐Kun
Abstract: With increasing energy demands worldwide, significant efforts have been made to develop superior electrocatalysts for efficient energy conversion systems. Among all the electrocatalysts exploited, Pt‐based bimetallic nanomaterials stand out by virtue of their high catalytic activity and relatively low cost due to the introduction of a nonprecious metal component. It should be noted that electrocatalytic reactions only take place on the surface of catalysts, so investigations of the surface composition of Pt‐based bimetallic nanomaterials are necessary for practical electrocatalysts. In this review, recent studies on controlling the surface composition of Pt‐based bimetallic catalysts for the oxygen reduction reaction, formic acid electrooxidation, and ethanol electrooxidation are summarized. The controlling strategies, including the chemical method and the electrochemical method, are discussed. The impacts of surface composition compositions on the electrocatalytic performance are also discussed. Finally, the challenges and future directions for controlling the surface composition of Pt‐based bimetallic nanomaterials are addressed. Abstract : The recent progress in controlling the surface composition of Pt‐based bimetallic (PtM) nanomaterials is discussed. These surfaces directly impact the corresponding electrocatalytic reactions, for example oxygen reduction reactions, ethanol oxidations, and formic acid oxidations. This study also provides guidelines for researchers to pursue more efficient strategies to rationally design highly activity and stabile electrocatalysts.